A constitutionalist critique of the objective character of the infringement proceedings and a case for a "constitutional defence" - Bardutzky, Samo (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2019)
The article explores the implications of the (non)implementation of Directive 2006/24/ EC, which regulated the compulsory retention of traffic data. The central problem is whether the Member States should suffer financial burdens because they have not implemented the directive due to constitutional concerns. In the case of mandatory retention of traffic data, this problem is especially severe, as the constitutional objection that has been developed in some Member States have proved to be justified. Despite the concerns, the Commission was consistent in ensuring the implementation of the Directive. The article presents the characteristics of the court procedure for violation of EU law in the event of non-implementation of a directive and its objective nature, which prevents the Member States from arguing legal, financial or practical obstacles to implementation. In cases where obstacles are of constitutional nature, the author proposes the creation of a constitutional defence, which would prevent the imposition of financial sanctions in the event of non-implementation of the directive, while preserving the duty of the Member States to comply with the acquis.
Keywords: denarna kazen; Directive 2006/24/EC; Direktiva 2006/24/ES; fine; hramba; infringement of EU law; kršitev prava EU; prometni podatki; retention; traffic data